Short-term outcomes of Ozaki procedure: a multicenter study - I. I. Chernov; S. T. Enginoev; R. N. Komarov; V. V. Bazylev; D. G. Tarasov; K. B. Kadyraliev; D. S. Tungusov; A. V. Arutyunyan; A. V. Chragyan; P. A. Batrakov; A. M. Ismailbaev; B. M. Tlisov; et al. (Российский кардиологический журнал, 2021)
Aim. To analyze the short-term outcomes of Ozaki procedure.Material and methods. This retro-prospective multicenter study included 724 patients with aortic valve (AV) disease, who underwent AV neo-cuspitization (AVNeo) from 2015 to 2019. The register included 395 (54,5%) men and 329 (45,5%) women. The median age of patients was 63 (57-67) years (minimum age, 10 years; maximum age, 83 years). A total of 496 (68,6%) patients had aortic stenosis, 44 (6%) — aortic regurgitation, 184 (25,4%) — aortic stenosis and regurgitation. Infective endocarditis as a cause of AV disease was diagnosed in 23 (3,2%) patients. NYHA class III-IV heart failure was in 348 (48%) patients. Atrial fibrillation was registered before surgery in 141 (19,5%) patients.Results. In total, 314 (43,4%) patients underwent a single intervention (AVNeo), while the remaining 410 (56,6%) patients underwent combined operations. Access to the heart was performed through a median sternotomy in 687 (95%) patients, and in 37 (5%) patients through a ministernotomy. The median cardiopulmonary bypass time was 130 (110-130) min, while the myocardial ischemic time — 104 (86-122) min. In-hospital mortality was 1,6%. The maximum and mean pressure gradient after surgery were 10,9 (7,4-14,8) mm Hg and 5,3 (3,5-7,3) mm Hg, respectively. The AV effective orifice area (EOA) and indexed EOA after surgery were 3 (2,5-3,9) cm2 and 1,6 (1,3-2) cm2/m2, respectively. Thirteen (1,8%) patients received a pacemaker. Acute renal failure was recorded in 4 (0,5%) patients, stroke — in 3 (0,4%), and sternal infection — in 10 (1,4%).Conclusion. The Ozaki procedure is feasible and reproducible, has good shortterm outcomes with excellent hemodynamic parameters. Further research is needed to assess long-term results.